If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + 2p) + 7 = -4(p + 2) (1 * 3 + 2p * 3) + 7 = -4(p + 2) (3 + 6p) + 7 = -4(p + 2) Reorder the terms: 3 + 7 + 6p = -4(p + 2) Combine like terms: 3 + 7 = 10 10 + 6p = -4(p + 2) Reorder the terms: 10 + 6p = -4(2 + p) 10 + 6p = (2 * -4 + p * -4) 10 + 6p = (-8 + -4p) Solving 10 + 6p = -8 + -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. 10 + 6p + 4p = -8 + -4p + 4p Combine like terms: 6p + 4p = 10p 10 + 10p = -8 + -4p + 4p Combine like terms: -4p + 4p = 0 10 + 10p = -8 + 0 10 + 10p = -8 Add '-10' to each side of the equation. 10 + -10 + 10p = -8 + -10 Combine like terms: 10 + -10 = 0 0 + 10p = -8 + -10 10p = -8 + -10 Combine like terms: -8 + -10 = -18 10p = -18 Divide each side by '10'. p = -1.8 Simplifying p = -1.8
| 12(3x+5)-5(2x-2)=6x-50 | | (2x+5)/(2)-(3x)/(x-2)=x | | 3x+51=12 | | 2x+4/3x+6 | | .06x+.03(7000-x)=249 | | 3y-2y+1=9 | | .19y+.06(y+7000)=1420 | | 9x+5=18-4 | | 4a-a+2=17 | | 2m^2=2 | | 3.6x+8.1=1.7x+25.2 | | 2(r-2)(r-5)-(r+4)(2r-6)= | | 2x^2+8-42=0 | | 2x^2+4x-17=0 | | -15x+17=7x-7 | | 655=430+0.03t | | -18-(-20)= | | 43x-21-5x=18+38x-39 | | 1545=170+0.11t | | 5x+17=7x-23 | | 3n^2-84=-4n | | -16t^2+484=h | | 810=250+0.07t | | -15-(-18)= | | 710=310+0.04t | | 4x^2-14x+49=0 | | 18g-13g+1=11 | | 2x-5(x-3)=-9+4x+3 | | 4(r-12)=16 | | 3x+3=3(x+4)-4 | | 5b+4b=-17 | | 6x+2=-7+2x+17 |